TAKSONOMI BLOOM DALAM PERSPEKTIF AL-QURAN (STUDI ANALASIS TERHADAP QS. AL-BAQARAH: 129 DAN 151) - Sabiq, Ahmad Musyafa'; Maksum, Ali (Geneologi PAI: Jurnal Pendidikan Agama Islam, 2025)
Abstract. This study aims to examine Bloom's Taxonomy which classifies the domain of educational objectives into three domains; cognitive, affective, and psychomotor. Compared with the interpretation of the scholars of tafsir on Surah Al-Baqarah verse 192 and 151. The background of this study is the urgency of contemporary Islamic education, still referring to the educational values contained in the main source of Islamic education, namely the Qur'an. This study uses a qualitative-descriptive approach with a library research method as the main technique in data collection and analysis. The results of the study show that between the theory of Bloom's Taxonomy and the Taxonomy of Islamic Education from the Perspective of the Qur'an there are similarities and conformities. The cognitive domain related to the ability and skills of thinking intelligence, in line with the meaning of tilâwatu âyâtillâh (reading the verses or signs of God's power). While the affective domain related to emotions, attitudes, values, and feelings in accordance with the meaning of the verse at-tazkiyah (purification). And the psychomotor domain, related to job skills, involves body movement, in accordance with one of the meanings of the phrase "ta'lîmul al-kitab wa al-hikmah" (teaching the Quran and wisdom). The conclusion of this study confirms that the Quran aligns with modern science and does not conflict with natural human needs.